Global Global Phenomenon of Performance and Profit Growth on Stock Price of LQ-45 Companies in Indonesia During The Covid 19 Pandemic - Erwin Harinurdin (Jurnal Keuangan dan Perbankan (KEBAN), 2023)
The emergence of the Covid-19 outbreak accelerating human behavior using digitalization as the main instrument. During the Covid-19 pandemic, the virtual world has become much busier than before. Communities switch to using gadgets and computers as the main tools to replace various activities directly. These changes in society have an impact on economic development by accelerating its digital transformation. The pandemic has led to a further acceleration of digital transformation globally. The company seeks to improve its company in order to get the maximum profit from its business activities . Companies that are able to improve their performance can be said that these companies are capable of competing with other companies so that efficiency occurs . The purpose of this study is to determine the effect of Current Ratio, Net Profit Margin, Return On Assets , and Company Age on Profit Growth and the Effect of Profit Growth on Stock Prices on the Indonesia Stock Exchange 2018-2021. This research includes a quantitative type. The population in this study are companies on the LQ45 index listed on the Indonesia Stock Exchange in the 2018-2021 period with a total sample of 34 companies. This study used a purposive sampling method. data analysis using comparative analysis and multiple linear regression analysis . The results showed that simultaneously the current ratio, net profit margin, return on assets, firm age have a positive effect on profit growth . Profit growth no significant effect on stock prices . Variable Net Profit Margin (NPM) and Return On Assets (ROA) have a significant influence on profit growth. While profit growth has no significant effect on profit growth. The results of the comparative analysis show that there is no statistically significant difference between the values of the Current Ratio, Net Profit Margin, Return On Assets, Profit Growth and Stock Prices between Covid and before Covid.